Novel evidence of CNV deletion in KCTD13 related to the severity of isolated hypospadias in Chinese population - Chen, Yijing; Zhou, Lijun; Chen, Fang; Chen, Zhongzhong; Huang, Yichen; Lv, Yiqing; Wu, Min; Lin, Xiaoling; Xie, Hua (Frontiers in Pediatrics, 2024)
Background CNV in KCTD13 has been identified to influence androgen receptor function via its changes in gene dosage, which might contribute to hypospadias. However, there is lack of population-level evidence to assess the contribution of KCTD13 CNV to hypospadias. Methods 349 isolated hypospadias patients were recruited and their genotyping was performed using real-time qPCR. We use Database of Genomic Variants (DGV) and CNV calls from SNP-array intensity data in 1,008 Chinese healthy men as reference. Results 11.17% of patients were identified to have KCTD13 CNV deletion, significantly higher than 0.05% in DGV (P < 0.001), but no cases found to have CNV duplication. Meanwhile, no CNV calls encompassing KCTD13 region were detected in Chinese healthy men. Incidence of KCTD13 CNV deletion was significantly increased with the severity of hypospadias, P_trend = 9.00 × 10−6. Compared to distal hypospadias, ORs for the proximal and midshaft were 10.07 (2.91–34.84) and 6.08 (1.69–21.84) respectively. In addition, the association between genital characteristics (stretched penile length and glans width) and KCTD13 CNV showed no significance in hypospadias children (P > 0.05). Conclusions We demonstrate KCTD13 CNV deletion is strongly associated with hypospadias and its severity, but duplication is not, characterizing KCTD13 genetic variation in more detail than previously described.